Assessing Loss on ignition to determine organic matter in soils of the El Oro province of Ecuador. - BARREZUETA-UNDA, S. (Universidad Nacional del Litoral, 2020)
The Loss On Ignition (LOI) method is used to estimate the soil organic matter (SOM) but has its advantages and limitations compared to other methods that calculate it from organic carbon (OC). The objective of the work was to calibrate the LOI method for use in alluvial soils cultivated with cocoa (Theobroma cacao L.). Thirty soil samples were extracted from 0 to 30 cm depth, and the following were determined SOM by LOI at 350, 430 and 600°C for 2h. These samples werecontrasted with the dry combustion (DC) and Walkley and Black (WB) methods for OC determinations. The values obtained by LOI increased from 3,46% <4,95%<7,66%, when the temperature increased, being lower than those obtained with DC (1,85%) and WB (1,96%). The best linear adjustment obtained between LOI and DC was, at 430°C with an explanation coeffi cient (R2) equal to 0.83. Although the LOI method at 430°C was the best fi t to be used in the SOM calculation, more repetitions should be done for a better calibration model.